PENGARUH MOTIVASI BISNIS TERHADAP KINERJA USAHA MIKRO KECIL MENENGAH PADA USAHA DAGANG DI KECAMATAN LUAHAGUNDRE MANIAMOLO - Fau, Deswinta Feronika (LPPM Universitas Nias Raya, 2024)
The purpose of this study is to determine the Influence of Business Motivation on the Performance of Micro Small Medium Enterprises in Trading Businesses in Luahagundre Maniamolo District. This research uses a quantitative approach. The type of data used in this study is primary data obtained directly from respondents. The data source used in this research is from trading business operators using questionnaires, with a population and sample of 32 respondents. The data collection technique is through questionnaires, providing a list of statements for respondents to fill out. The data analysis method used is simple regression analysis. Based on the hypothesis testing results with a t-value of 4.069 > t-table = 1.694, it means there is an influence of business motivation on the performance of Micro Small Medium Enterprises in Trading Businesses in Luahagundre Maniamolo District. This study concludes that there is an influence of business motivation on the performance of Micro Small Medium Enterprises in Trading Businesses in Luahagundre Maniamolo District. Suggestions from this research are: (1) To enhance business performance, especially in Luahagundre Maniamolo District, the government should provide motivation to micro-business operators through loans with relatively low interest rates to facilitate community economic circulation. (2) The commitment of micro-business operators in their activities should be increased to boost sales volume. (3) In achieving the success of micro-businesses in Luahagundre Maniamolo District, sales facilities should be equipped according to community needs. (4) Trading business conditions improve when business operators provide good service supported by business capital.